A single-center observational study on congenital diaphragmatic hernia: Outcome, predictors of mortality and experience from a tertiary perinatal center in Singapore - Wan-Yee Teo; Bhavani Sriram; AA Abdul Alim; Xucong Ruan; V.S. Rajadurai (Elsevier, 2020)
Background: Congenital diaphragmatic hernia (CDH) is a common birth defect associated with significant mortality and morbidity. There is limited outcome data on CDH in the Southeast Asian region. Rapid accessibility to our CDH Perinatal Center, as a consequence of the small geographic size of our country and efficient land transportation system, has largely eliminated deaths of live outborn babies prior arrival at our center. We selected a study period when extracorporeal membrane oxygenation (ECMO) support was not available at our institution. The data will therefore be relevant in developing management guidelines and antenatal counselling for perinatal centers in this region managing CDH with limited resources, without ECMO facilities. Methods: A retrospective study of antenatally or postnatally diagnosed CDH infants born between January 2002 and June 2005 was performed. We selected this study period as ECMO support was not available over this period. We studied the demographics, clinical characteristics, postnatal predictors of mortality and outcomes of CDH infants in a single tertiary institution. Results: A total of 24 patients with CDH were identified. Seventy-nine percent of liveborns with CDH survived to hospital discharge. Antenatal detection rate was 83.3%. Significant postnatal predictors of mortality were preoperative pneumothorax (p = 0.035), high CRIB score (p = 0.007), low one- and five-minute Apgar score (p = 0.011, p = 0.026 respectively) and high pCO2 on initial arterial blood gas (p = 0.007). At one-year follow-up, three patients had delayed gross motor milestones which resolved subsequently. Re-admissions were required for recurrent bronchiolitis (33%) and oesophageal reflux which resolved in all cases. Two (13.3%) infants had surgical complications and needed re-admission for probable adhesive intestinal obstruction; one required adhesiolysis and the other was managed conservatively with good outcome. Conclusion: A single-center CDH outcome in Singapore, without ECMO use, was good. This is a cohort now with long-term survival outcome which will be valuable to the neonatology community.